Conflict of Interest Policies and Industry Relationships of Guideline Development Group Members: A Cross-Sectional Study of Clinical Practice Guidelines for Depression. (17th February 2017) - Cosgrove, Lisa; Krimsky, Sheldon; Wheeler, Emily E.; Peters, Shannon M.; Brodt, Madeline; Shaughnessy, Allen F.
ABSTRACT: Because of increased attention to the issue of trustworthiness of clinical practice guidelines, it may be that both transparency and management of industry associations of guideline development groups (GDGs) have improved. The purpose of the present study was to assess a) the disclosure requirements of GDGs in a cross-section of guidelines for major depression; and, b) the extent and type of conflicts of panel members. Treatment guidelines for major depression were identified and searched for conflict of interest policies and disclosure statements. Multi-modal screens for undeclared conflicts were also conducted. Fourteen guidelines with a total of 172 panel members were included in the analysis. Eleven of the 14 guidelines (78%) had a stated conflict of interest policy or disclosure statement, although the policies varied widely. Most (57%) of the guidelines were developed by panels that had members with industry financial ties to drug companies that manufacture antidepressant medication. However, only a minority of total panel members (18%) had such conflicts of interest. Drug company speakers bureau participation was the most common type of conflict. Although some progress has been made, organizations that develop guidelines should continue to work toward greater transparency and minimization of financial conflicts of interest.